The Assistance of The School Health Unit "UKS" Development to Optimize Health Among Elementary Students - Henik Tri Rahayu; Anis Ika Nur Rohmah (Asian Journal of Community Services, 2023)
School health units (in Indonesian abbreviation as "UKS") in educational institutions can sustain healthy behavior and optimize student growth and development. The lack of UKS facilities and no particular UKS supervisors resulted in several health problems among the school members. From these problems, the solutions offered by this community service activity included: support for optimizing/revitalizing UKS functions and health education/counseling related to existing problems to support or improve the health of school members, especially students. This community service has been carried out by providing training and coaching for UKS cadres in the context of empowering UKS cadres to support health in schools. The training materials include first aid management, wound care, and healthy foods. This community service's outcomes include increasing partners' knowledge and skills.